Medieval Monasticism in Northern Europe - Kristjánsdóttir, Steinunn (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
While the Christian monastic tradition and its development on the mainland of Europe has been extensively studied by scholars, medieval monasticism in Northern Europe has gained considerably less attention. However, interest in the topic has grown steadily, as can be observed from the varied research that has taken place during the last decades. This growing interest can partly be explained by the current multidisciplinary approaches in academic research as well as the emergence of studies on material culture and its entwinement with archival material during the last decades of the twentieth century. It may also be further explained by an increased awareness of how North-European historiography, including medieval monastic studies, has since the nineteenth century been shaped by Protestant views, albeit in combination with longstanding nationalistic political perspectives. Therefore, the topic needs to be revisited, as is done here, not least due to the growing multinational and religious tolerance apparent in present academic studies of humanities. By highlighting Northern Europe specifically, the issue aims also to place medieval monasticism in a broader geographical and cultural context as being one of the active agents that formed the Christian worldview of the Middle Ages. The overall ambition of this Special Issue is, at the same time, to emphasize and introduce novel approaches to the reciprocal formation of the pan-European monasticism through its shifting localities and temporality.